Frequency‐Division Multiplexing in Magnonic Logic Networks Based on Caustic‐Like Spin‐Wave Beams. Issue 12 (12th October 2018) - Heussner, Frank; Nabinger, Matthias; Fischer, Tobias; Brächer, Thomas; Serga, Alexander A.; Hillebrands, Burkard; Pirro, Philipp
Abstract : Wave‐based data processing by spin waves (SW) and their quanta, magnons, is a promising technique to overcome the challenges which CMOS‐based logic networks are facing nowadays. The advantage of these quasi‐particles lies in their potential for the realization of energy efficient devices on the micro‐ to nanometer scale due to their charge‐less propagation in magnetic materials. In this paper, the frequency dependence of the propagation direction of caustic‐like spin‐wave beams in microstructured ferromagnets is studied by micromagnetic simulations. Based on the observed alteration of the propagation angle, an approach to spatially combine and separate spin‐wave signals of different frequencies is demonstrated. The presented magnetic structure constitutes a prototype design of a passive circuit enabling frequency‐division multiplexing (FDM) in magnonic logic networks. It is verified that spin‐wave signals of different frequencies can be transmitted through the device simultaneously without any interaction or creation of spurious signals. Due to the wave‐based approach of computing in magnonic networks, the technique of FDM can be the basis for parallel data processing in single magnonic devices, enabling the multiplication of the data throughput. Abstract : The developed prototype design of a multi‐frequency spin‐wave circuit on the micrometer scale can help to drastically enhance the throughput of wave‐based logic networks. Utilizing the frequency dependence of the propagation direction of caustic‐like spin‐wave beams enables the combination and separation of spin waves of different frequencies, which can be used for simultaneous data processing in single devices.